A lesson learned from the integration of BIM in construction engineering education in an Indonesian Polytechnic - Abdi Suryadinata Telaga (Jurnal Pendidikan Vokasi, 2022)
The Indonesian construction industry has increasingly adopted Building Information Modeling (BIM). One of the barriers to adopting BIM is BIM skills among graduates are still rare. Therefore, higher education institutions have to adopt BIM into their curriculum. However, as BIM is a new concept in construction engineering, many higher education institutions have a problem integrating BIM. Therefore, the paper proffers a syllabus to integrate BIM in a vocational higher education institution. The research methodology follows the Tyler model of curriculum development. It started with a review of prominent BIM integration into higher education research. Then, discussion with BIM practitioners from the industry to acquire information on current BIM-related job specifications in Indonesia. The team teacher then discussed and analyzed the results to create an initial syllabus. Further, the students' performance and feedback are observed during two years of course offering from 2019 to 2021. Improvement of the syllabus is based on observation and feedback results. The progress has increased students' performance in the BIM course. The students' performance is excellent even though the course was offered online due to a pandemic.